2017
DOI: 10.1007/s00062-017-0633-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Neurography

Abstract: Quantitative biomarkers of MRN co-vary with demographic variables. As particularly important determinants, we identified body weight for nerve CSA and BMI for PSD. The presented normal values and demographic determinants may assist investigations into the potential of MRN biomarkers in further disease-specific studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…Our method could assist clinicians by providing a quantification of nerve volume, CSA, and lesion burden through a combination of morphometry and signal intensity analysis as shown in Figure 5 . Such analyses might allow distinguishing between healthy nerve and diseased nerve, and peripheral neuropathy type as it has been shown by others ( 5 , 7 11 ). Additionally, our segmentation could serve as a volume of interest for other quantitative MR methods like diffusion-weighted imaging, magnetization transfer imaging, and relaxometry ( 3 8 , 10 ), which might further be applied to assess total lesion burden, distribution pattern of lesions, and multi-model characterization of lesions.…”
Section: Discussionmentioning
confidence: 86%
“…Our method could assist clinicians by providing a quantification of nerve volume, CSA, and lesion burden through a combination of morphometry and signal intensity analysis as shown in Figure 5 . Such analyses might allow distinguishing between healthy nerve and diseased nerve, and peripheral neuropathy type as it has been shown by others ( 5 , 7 11 ). Additionally, our segmentation could serve as a volume of interest for other quantitative MR methods like diffusion-weighted imaging, magnetization transfer imaging, and relaxometry ( 3 8 , 10 ), which might further be applied to assess total lesion burden, distribution pattern of lesions, and multi-model characterization of lesions.…”
Section: Discussionmentioning
confidence: 86%
“…To the authors' knowledge, normal T2 values of the sciatic nerve have been primarily gathered from few control groups of healthy subjects or asymptomatic patients that were formed for comparisons to diseased cohorts with symptoms, with only one recent study being available to date that aimed on the distinct exploration of normal T2 values of the sciatic nerve [31]. This study investigated 60 healthy individuals by applying a MESE sequence for T2 relaxometry at 3 Tesla and demonstrated physiological T2 values in 5 men and 5 women of every decade between 20 and 80 years [31]. The study reported mean T2 values of 70.85 ± 4.91 ms [31].…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated 60 healthy individuals by applying a MESE sequence for T2 relaxometry at 3 Tesla and demonstrated physiological T2 values in 5 men and 5 women of every decade between 20 and 80 years [31]. The study reported mean T2 values of 70.85 ± 4.91 ms [31]. These values are, however, clearly higher in comparison to the T2 values obtained with the 3D T2-prepared TSE sequence in the present study, which were 44.6 ± 3.0 ms for the left and 44.5 ± 2.6 ms for the right distal sciatic nerve (according to measurements of R1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations